2008
DOI: 10.1002/ajhb.20780
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, overweight status, and perceptions of food insecurity among homeless Minnesotan youth

Abstract: Youth, 9-18 years (n = 202), living in homeless shelters in Minneapolis, Minnesota, were assessed for height, weight, dietary intake, and perceptions of food insecurity. Perceptions of food security were measured by asking youth to respond to the statements (1) "There are times when we do not have enough food in the house," (2) "I go to bed hungry at night," (3) "I do not get enough to eat at home," and (4) "Have you ever had to miss a meal (or not been able to eat) because there was no food at home?" Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 80 publications
1
70
0
2
Order By: Relevance
“…Similarly, a 2008 study of 202 homeless Minnesotan youths aged 9-18 years found that 45% of boys and 50% of girls were overweight (BMI >95%) or at risk of overweight (BMI >85% and <95%), rates that are substantially higher than national rates, yet many of them reported at least some level of food insecurity [33 ]. Moreover, certain questionnaire responses relating to food insecurity were predictive of increased BMI in girls ('if I am hungry, I will eat foods I do not like' and 'there are times when we do not have enough food in the house') and boys ('when I am hungry I will eat anything') [33 ]. It has been hypothesized that food insecurity may be associated with overweight due to the fact that food-insecure households consume more low-cost, high-energy dense foods, including nutrient poor, calorie-dense snack foods [37].…”
Section: Food Insecurity and Childhood Obesitymentioning
confidence: 95%
“…Similarly, a 2008 study of 202 homeless Minnesotan youths aged 9-18 years found that 45% of boys and 50% of girls were overweight (BMI >95%) or at risk of overweight (BMI >85% and <95%), rates that are substantially higher than national rates, yet many of them reported at least some level of food insecurity [33 ]. Moreover, certain questionnaire responses relating to food insecurity were predictive of increased BMI in girls ('if I am hungry, I will eat foods I do not like' and 'there are times when we do not have enough food in the house') and boys ('when I am hungry I will eat anything') [33 ]. It has been hypothesized that food insecurity may be associated with overweight due to the fact that food-insecure households consume more low-cost, high-energy dense foods, including nutrient poor, calorie-dense snack foods [37].…”
Section: Food Insecurity and Childhood Obesitymentioning
confidence: 95%
“…We reviewed 21 studies from higher income countries that examined the association between food insecurity and child nutritional status (Alaimo et al, 2001;Casey et al, 2001;Kaiser et al, 2002;Matheson et al, 2002a;Jones et al, 2003;Bhattacharya et al, 2004;Jyoti et al, 2005;Casey et al, 2006;Dubois et al, 2006;Rose and Bodor, 2006;Martin and Ferris, 2007;Smith and Richards, 2008;Gundersen et al, 2008aGundersen et al, ,b,2009Metallinos-Katsaras et al, 2009;Yu et al, 2010). Of those, 13 reported no relationship between food insecurity and child overweight or obesity; although many included multiple subgroup tests that revealed ''pockets'' of statistical significance.…”
Section: Food Insecurity and Nutritional Status In Childrenmentioning
confidence: 99%
“…From a theory-building perspective, studies that compare two or more populations will likely generate the most insight into how and why food insecurity impacts health and wellbeing, and how individual, household, and community-level variables promote or erode food security. Some populations that would be of particular interest to USbased anthropologists and where excellent foundational work exists include studies on drug users (e.g., Himmelgreen et al, 1998), homeless persons (e.g., Smith and Richards, 2008), migrants (e.g., Quandt et al, 2006;Himmelgreen et al, 2007;Patil et al, 2010), unemployed and underemployed, and the elderly (e.g., Quandt and Rao, 1999;Wolfe and Frongillo, 2003). These latter two populations might be particularly interesting giving global economic and demographic trends.…”
Section: Marginalized Populationsmentioning
confidence: 99%
“…In adults, food insecurity has been clearly associated with increased obesity, particularly in women. 4,5 In children, many studies have demonstrated increased risk of obesity, [6][7][8][9][10][11][12][13] although the results have been mixed. 4,5,[14][15][16][17][18][19] Less research has explored potential pathways through which household food insecurity is related to child weight, especially in families with young infants.…”
mentioning
confidence: 99%